Pengaruh Intellectual Capital Terhadap Financial Performance Dengan Competitive Advantage Sebagai Variabel Moderasi (Jurnal Ekonomi Bisnis dan Akuntansi, 2023)
This research aims to test and analyze the influence of intellectual capital on financial performance with competitive advantage as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2022. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange in 2022 The sampling technique used purposive sampling technique, with 172 companies in this study. The analysis technique used is multiple linear regression using SPSS version 26 software. The results of this research prove that there is a positive influence of Intellectual Capital on Financial Performance. Competitive Advantage is able to moderate the relationship between Intellectual Capital and Financial Performance.